A new group of anti-lipopolysaccharide factors from Marsupenaeus japonicus functions in antibacterial response. Issue 1 (January 2015) - Jiang, Hai-Shan; Zhang, Qing; Zhao, Yan-Ran; Jia, Wen-Ming; Zhao, Xiao-Fan; Wang, Jin-Xing
Highlights A new group of ALFs (MjALF-E1 and E2) was identified in Marsupenaeus japonicus. Both MjALF-E1 and E2 were upregulated by G+ and G− bacterial challenge. MjALF-E1 and E2 strongly bind to bacterial cell wall components LPS and PGN. MjALF-E2 exhibited antimicrobial activity against Gram-negative bacteria. MjALF-E2 promotes the clearance of bacteria in shrimp.